Urethral leak: an unusual symptom of pudendal nerve entrapment - Afonso Ramos, Sónia (Cent European J Urol, 2020)
Pudendal nerve (PN) entrapment is one of the most misunderstood and underdiagnosed medical conditions. It is recognized as a cause of chronic pelvic pain syndrome. However, due to the pudendal nerve’s mixed composition and complex anatomy, the presenting symptoms are varied and go beyond pain, depending on the entrapment’s nature, location and duration. We report a unique case of a young patient presenting with a urethral leak refractory to antibiotics. Patient evaluation highlighted findings suspicious of pudendal nerve entrapment. The patient was submitted to a laparoscopic transperitoneal PN neurolysis, resulting in major symptoms improvement.